A experiência do movimento de ouvidores de vozes em Brasília/DF - Willrich, Janaína Quinzen; Pickersgill, Mirela Farias; Portela, Dariane Lima; da Cruz, Márcio Santos (Journal of Nursing and Health, 2018)
-